Pengaruh Efektivitas Kebijakan Fintech Terhadap Inklusi Keuangan Pelaku UMKM di Kota Padang - Rahma Fitri Azzahra; Boni Saputra (Policy, Law and Political Research Center, 2025)
This study aims to analyze the effectiveness of financial technology (fintech) policies on the financial inclusion of MSMEs in Padang City by identifying causal mechanisms and quantifying their contribution. The research method used an associative quantitative approach, with probability sampling techniques and simple random sampling of 100 MSME respondents, a structured questionnaire tested for validity and reliability, and simple linear regression analysis in SPSS version 26. The results show that the effectiveness of fintech policies has a positive and significant effect on the financial inclusion of MSME players with a regression coefficient of 0.786, a t-value of 13.931, a significance of 0.000, and a coefficient of determination of 66.4%, indicating that increasing the effectiveness of fintech policies through regulatory strengthening, stakeholder coordination, and technology adaptation will improve access to and utilization of digital financial services. The implications of this study provide strategic recommendations for regulators to strengthen monitoring of policy implementation at the local level, for local governments to intensify digital financial literacy programs and the provision of technological infrastructure, and for fintech providers to develop products that are more accessible to the micro MSME segment to achieve equitable and sustainable financial inclusion.